Bioethics, Gender and Human Development in the Brazilian Educational Process (Revista Iberoamericana de Bioética, 2019)
This article takes a Bioethics approach to topics linking gender issues and Primary Education, in teachers of Elementary School I and II of public and private schools in the municipality of Pouso Alegre-MG. It uses a content analysis method, which combines a thorough bibliographic research with a semi-structured survey applied to eighteen teachers from two public and one private schools. A lack of teacher knowledge regarding bioethics and dialogue on gender issues was found, possibly due to the absence of graduate-level courses on bioethical approaches to gender issues. Arguments offered by teachers also demonstrated unfamiliarity with the subject. It is concluded that bioethical knowledge in pedagogical practice is necessary for education forged in a society of prejudice.